The Strawberry FaWRKY1 Transcription Factor Negatively Regulates Resistance to Colletotrichum acutatum in Fruit Upon Infection - Higuera, José Javier; Garrido-Gala, José; Lekhbou, Ayman; Arjona-Girona, Isabel; Amil-Ruiz, Francisco; Mercado, José A.; Pliego-Alfaro, Fernando; Muñoz-Blanco, Juan; López-Herrera, Carlos J.; Caballero, José L. (Frontiers in Plant Science, 2019)
Abstract Strawberry (Fragaria x ananassa) is a major food crop worldwide, due to the flavor, aroma and health benefits of the fruit, but its productivity and quality are seriously limited by a large variety of phytopathogens, including Colletotrichum spp. So far, key factors regulating strawberry immune response remain unknown. The FaWRKY1 gene has been previously proposed as an important element mediating defense responses in strawberry to C. acutatum. To get further insight into the functional role that FaWRKY1 plays in the defense mechanism, Agrobacterium-mediated transient transformation was used both to silence and overexpress the FaWRKY1 gene in strawberry fruits (Fragaria x ananassa cv. Primoris), which were later analyzed upon Colletotrichum acutatum inoculation. Susceptibility tests were performed after pathogen infection comparing the severity of disease between the two agroinfiltrated opposite halves of the same fruit, one half bearing a construct either for FaWRKY1 overexpression or RNAi-mediated silencing and the other half bearing the empty vector, as control. The severity of tissue damage was monitored and found to be visibly reduced at five days after pathogen inoculation in the fruit half where FaWRKY1 was transiently silenced compared to that of the opposite control half and statistical analysis corroborated a significant reduction in disease susceptibility. Contrarily, a similar level of susceptibility was found when FaWRKY1 overexpression and control fruit samples, was compared. These results unravel a negative regulatory role of FaWRKY1 in resistance to the phytopathogenic fungus Colletotrichum acutatum in strawberry fruit and contrast with the previous role described for this gene in Arabidopsis as positive regulator of resistance against the bacteria Pseudomonas syringae. Based on previous results, a tentative working model for WRKY75 like genes after pathogen infection is proposed and the expression pattern of potential downstream FaWRKY1 target genes was also analyzed in strawberry fruit upon C. acutatum infection. Our results highlight that FaWRKY1 might display different function according to species, plant tissue and/or type of pathogen and underline the intricate FaWRKY1 responsive defense regulatory mechanism taking place in strawberry against this important crop pathogen.